Tilted fiber Bragg grating based optical sensor for simultaneous measurement of vital signs: a novel approach - Arumugam, Ramya; Kumar, Ramamoorthy; Dhanalakshmi, Samiappan (Institute of Advanced Engineering and Science, 2025)
Vital signal monitoring acts as a highly significant diagnostic method. Continuous monitoring of vital signs like temperature, heart rate, and blood pressure aids in easy and fast disease diagnosis. Existing methods that enable continuous monitoring, such as smart watches, are not accurate enough to be used as a benchmark for diagnosing diseases. In this paper, we propose simultaneous temperature and heart rate measurement using tilted fiber Bragg grating (TFBG) which enables concurrent measurement of measurands due to its intrinsic optical property. Temperature and heart rate were considered for measurement. The proposed TFBG-based optical sensor has a sensitivity of 11.81 pm/°C and 1.73 pm/µε towards variation in temperature and strain, respectively. The sensitivity was determined by a shift in the wavelength of core mode resonance for temperature and a differential change in the wavelength of cladding mode resonance for heart rate. The average response time of the proposed TFBG sensor was found to be 3 seconds. Accuracy of 99.68% and 98.42% were achieved in temperature and heart rate measurements by the proposed TFBG sensor. The acceptability of the proposed TFBG sensor was analyzed using the Bland- Altman plot.